Crustal thickness and support of topography on Venus. Issue 4 (30th April 2013) - James, Peter B.; Zuber, Maria T.; Phillips, Roger J.
Abstract : [1] The topography of a terrestrial planet can be supported by several mechanisms: (1) crustal thickness variations, (2) density variations in the crust and mantle, (3) dynamic support, and (4) lithospheric stresses. Each of these mechanisms could play a role in compensating topography on Venus, and we distinguish between these mechanisms in part by calculating geoid‐to‐topography ratios and apparent depths of compensation. By simultaneously inverting for mass anomalies at two depths, we solve for the spatial distribution of crustal thickness and a similar map of mass anomalies in the mantle, thus separating the effects of shallow and deep compensation mechanisms on the geoid. The roughly circular regions of mantle mass deficit coincide with the locations of what are commonly interpreted to be buoyant mantle plumes. Additionally, there is a significant geographic correlation between patches of thickened crust and mass deficits in the mantle, especially for spherical harmonic degree l < 40. These mass deficits may be interpreted either as lateral thermal variations or as Mg‐rich melt residuum. The magnitudes of mass deficits under the crustal highlands are roughly consistent with a paradigm in which highland crust is produced by melting of upwelling plumes. The mean thickness of the crust is constrained to a range of 8–25 km, somewhat lower than previous estimates. The best two‐layered inversion of gravity incorporates a dynamic mantle load at a depth of 250 km. Key Points: Topography on Venus is supported through multiple mechanisms We calculate ratios of geoid to topography on Venus We invert the gravity field to make a map of crustal thickness